Clinical and laboratory assessment for the inflammation role in chronic spontaneous urticaria: A clinical study. Issue 6 (4th September 2020) - Ataseven, Arzu; Durmaz, Koray; Temiz, Selami Aykut; Dursun, Recep
Abstract: Chronic spontaneous urticaria (CSU) is triggered by unknown causes. We would like to explore the possible effect of hemogram parameters and several biochemical markers on CSU presence and also the severity of the disease. We also aimed to discuss the relationship between CSU and inflammation associated with these values. The study was planned prospectively. We selected patients already diagnosed with CSU who applied to the dermatology outpatient clinic and healthy controls. The patients and the healthy controls were tested for complete blood count, neutrophil/lymphocytes ratio and platelets/lymphocytes ratio, erythrocyte sedimentation rate, C‐reactive protein, serum albumin and total bilirubin and indirect bilirubin levels. Urticaria activity score over 7 days (UAS‐7) was calculated for the CSU patients. Forty patients with CSU and 55 healthy subjects were included in the study. Mean white blood cell (WBC) count is 8.37 ± 2.14 in the patients' group and 7.41 ± 2.01 in the healthy subjects group. Mean neutrophil (NEU) count is 4.88 ± 1.65 in the patients' group and 4.19 ± 1.39 in the healthy subjects group. Mean platelets (PLT) count is 308.48 ± 88.32 in the patients' group and 268.65 ± 64.80 in the healthy subjects group. We also detected positive correlations between UAS‐7 score‐WBC counts and UAS‐7 score‐NEU counts. Future studies are needed to investigate this possible relationship and confirm these results.